Transparency and fairness in school choice mechanisms - Yoan Hermstrüwer (Max Planck Institute for Research on Collective Goods, 2019)
This article explores the impact of procedural information on the behavior of applicants under two of the most commonly used school admissions procedures: the Gale-Shapley mechanism and the Boston mechanism. In a lab experiment, I compare the impact of information about the mechanism, information about individually optimal application strategies, and information about both. I find that strategic and full information increase truth-telling and stability under the Gale-Shapley mechanism. Under the Boston mechanism, however, the adoption of equilibrium strategies remains unaffected. Contrary to prevailing assumptions in matching theory, I show that the Boston mechanism improves perceived fairness. These results underscore the importance of procedural information and suggest that eliminating justified envy may not be a sufficient condition of fairness.
Keywords: C78; C92; D47; I20; K10; 330; matching markets; school choice; transparency; fairness; law and market design